Correlation Between the Forearm Plus Little Finger Length and The Actual Femoral Length (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the correlation between forearm plus little finger length and the actual femoral length in orthopedic patients presenting with femoral shaft fractures at a teaching hospital in Punjab. Design: Descriptive cross-sectional study. Place and Duration of Study: This study was conducted in the department of Orthopedic Surgery, Sir Ganga Ram Hospital, Lahore from November 2014 to June 2015. Patients and Methods: 30 patients of both genders, aged between 18-70 years having femoral shaft fractures undergoing intramedullary nail fixation at Department of Orthopedic Surgery, Sir Ganga Ram Hospital, Lahore were included in this study. A written informed consent was obtained from every patient. Results: The age of the patients ranged from 26 years to 59 years with a mean of 42.10±9.79 years. There were 27 (90%) male and 3 (10%) female patients in the study group. The forearm plus little finger length ranged from 38 cm to 44 cm with a mean of 40.97±2.28 cm. The actual femoral length ranged from 38 cm to 45 cm with a mean of 40.93±2.29 cm. The forearm plus little finger length correlated well (r=.970; p=.01) with the actual femoral length with a mean difference of .036. This correlation was unaffected by patient age (r=0.13, p=.183) and gender (t=-1.87, p=.096). Conclusion: Forearm plus little finger length strongly correlates (r=.970; p=.01) with the actual femoral length and can be used for pre-operative determination of femoral length in the management of patients with femoral shaft fractures.
Keywords: Femoral Shaft Fracture, Intramedullary Nail, Forearm plus Little Finger Length, Actual Femoral Length, Correlation